Al-Kitab fii ta'allum al-'Arabiyya: a texbook for beginning Arabic: Par One - BRUSTAD, Kristen (Georgetown Univ. Press, 1995)
Al-Kitab fii ta'allum al-'Arabiyya: a texbook for beginning Arabic: Part One